Chrono-Pharmacological Study of Once Daily Curative Dose of a Low Molecular Weight Heparin (200IU antiXa/kg of Dalteparin) in Ten Healthy Volunteers - Mismetti, P; Reynaud, J; Tardy-Poncet, B; Laporte-Simitsidis, S; Scully, M; Goodwyn, C; Queneau, P; Decousus, H (Thrombosis and Haemostasis, 1995)
Low molecular weight heparin (LMWH) is currently prescribed for the treatment of deep vein thrombosis at the dose of 100 IU antiXa/kg twice daily or at a dose of 175 IU antiXa/kg once daily with a similar efficacy. We decided to study the chrono-pharmacology of curative dose of LMWH once daily administrated according to the one previously described with unfractionated heparin (UFH).Ten healthy volunteers participated in an open three-period crossover study according to three 24 h cycles, separated by a wash-out interval lasting 7 days: one control cycle without injection, two cycles with subcutaneous injection of 200 IU antiXa/kg of Dalteparin (Fragmin®) at 8 a.m. or at 8 p.m. Parameters of heparin activity were analysed as maximal values and area under the curve.Activated partial thromboplastin time (APTT), thrombin time (TT), prothrombin time (PT) and tissue factor pathway inhibitor (TFPI) were higher after 8 p.m. injection than after 8 a.m. injection (p <0.05) while no chrono-pharmacological variation of anti factor Xa (AXa) activity was observed. Thus the biological anticoagulant effect of 200 IU antiXa/kg of Dalteparin seems to be higher after an evening injection than after a morning injection.A chrono-therapeutic approach with LMWH, as prescribed once daily, deserves further investigation since our results suggest that a preferential injection time may optimise the clinical efficacy of these LMWH.